2021
DOI: 10.1093/rheumatology/keab432
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis reveals three main patterns of beliefs and intention with respect to SARS-CoV-2 vaccination in patients with autoimmune and inflammatory diseases

Abstract: Introduction Given the COVID19 pandemic, it is crucial to understand the underlying behavioral determinants of SARS-CoV-2 vaccine hesitancy in patients with autoimmune or inflammatory rheumatic diseases AIIRD. We aimed to analyze patterns of behaviors regarding SARS-CoV-2 vaccination in AIIRD patients, as a mean to identify pragmatic actions to increase vaccine coverage in this population. Methods Data of 1258 AIIRD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
3
28
0
Order By: Relevance
“…Interestingly, similar to other investigators [12,29], we did not find any association between vaccination uptake and comorbidities and/or treatment in our cohort. On the other hand, in accordance with other investigators [23,30], we found that increased age was associated with willingness to vaccinate against COVID-19.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, similar to other investigators [12,29], we did not find any association between vaccination uptake and comorbidities and/or treatment in our cohort. On the other hand, in accordance with other investigators [23,30], we found that increased age was associated with willingness to vaccinate against COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…In line with this finding, more than half of the unvaccinated patients in our study were willing to reconsider their decision. Another study has described in more detail the thoughts that might make patients hesitant/suspicious of the COVID-19 vaccine [29]. To this end, patients' and clinicians' education about benefits of vaccination is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…These uncertainties have been shown to be major determinants of reduced vaccination willingness in patients with rheumatic and musculoskeletal diseases. 6 Therefore, the primary objective of the international vaccination against COVID in systemic lupus (VACOLUP) study was to assess the tolerance of COVID-19 vaccines in patients with SLE, including the risk of incident flare, from the patients' perspective.…”
mentioning
confidence: 99%
“…Willingness to get vaccinated against COVID-19 in patients with autoimmune diseases is limited by the fear of sideeffects and the paucity of available data. 6 Therefore, disseminating these reassuring data might prove crucial to increasing vaccine coverage in patients with SLE.…”
mentioning
confidence: 99%
“…The Arab League of Associations for Rheumatology (ArLAR) COVID Vaccination (ARCOVAX) cross-sectional study used an anonymous web-based survey adapted from the VAXICOV study, 3 , 6 translated to Arabic by the authors and validated by the ArLAR scientific committee. A pilot test done in three languages (Arabic, English, and French) found the survey to be well understood and easy to complete.…”
mentioning
confidence: 99%